Religiosity is associated with caregivers' perception of preschool children's dental health - Danielle Cristina Alves RIGO; Juliana Borges da Silva FERREIRA; Luciane Rezende COSTA; Maria do Carmo Matias FREIRE (Sociedade Brasileira de Pesquisa Odontológica, 2022)
Abstract The aim of the study was to investigate the association between psychosocial factors and perception of caregivers about the dental health of their preschool children. A cross-sectional analysis was performed with 146 caregiver-child dyads attended at Pediatric Dentistry school clinics in Goiânia, Midwest Brazil. Data were collected through a structured interview and a questionnaire with the caregivers and the children's dental records. The study outcome was caregivers' perception of children's dental health (positive or negative). The independent psychosocial variables were religiosity (Duke University Religion Index - DUREL) and Sense of Coherence (Antonovsky's SOC-13 scale). Sociodemographic data and oral health-related variables were also collected as covariates. Bivariate analysis (Pearson's chi-square, T-test, and Mann-Whitney) and Poisson regression with robust variance were performed. The prevalence of negative perception was 54.8%. In bivariate analysis, negative perception was associated with caries experience and report of dental pain at any time in the child's life. In the adjusted regression model, prevalence of caregivers with negative perception of their children's dental health was 1.38 times higher in the group with low organizational religiosity (PR = 1.38; 95%CI 1.05-1.81) and 2.35 times higher in the group of children with high caries experience (PR = 2.35; 95%CI 1.54-3.60). In conclusion, religiosity was associated with caregivers' perception of dental health of their preschool children undergoing treatment in specialized dental clinics, regardless of their caries experience.